The cricket in Times Square. - Selden, George, 1929-; Williams, Garth - illus (New York : Ariel Books, 1960)
With the help of a mouse and a cat, a musical cricket improves business at the newsstand run by Mario and his family.
Keywords: Crickets -- Fiction; Mice -- Fiction; Cats -- Fiction; Newbery honor book